Use of TRIZ principles in car design - Wu, Xinni. (2011)
With the vast advances in technology, there is a need for new ideas and design solutions. The body of design knowledge and the application of this knowledge to solving technical problems are expanding rapidly (Savransky, 2000). This results in a spreading need for educational institutions to teach the younger generation to be innovative and to solve technical and nontechnical problems more creatively.